2016
DOI: 10.1016/j.gaitpost.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of kinematic measures of the thoracic spine, lumbar spine and pelvis during fast running

Abstract: Please cite this article as: Mason DL, Preece SJ, Bramah CA, Herrington LC, Reproducibility of kinematic measures of the thoracic spine, lumbar spine and pelvis during fast running, Gait and Posture (2014), http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(79 citation statements)
references
References 20 publications
(29 reference statements)
5
71
1
2
Order By: Relevance
“…Similar to the lumbar spine, some investigators have used a marker wand, attached to the posterior aspect of the thorax . In contrast, a number of other studies have been performed using a set of skin-mounted markers placed at a range of different locations on the thorax (Seay et al, 2008;Mason et al, 2014). In a recent study (Mason et al, 2014) we demonstrated good reliability using a rigid plate attached directly to the sternum, as suggested by wu et al (2005).…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…Similar to the lumbar spine, some investigators have used a marker wand, attached to the posterior aspect of the thorax . In contrast, a number of other studies have been performed using a set of skin-mounted markers placed at a range of different locations on the thorax (Seay et al, 2008;Mason et al, 2014). In a recent study (Mason et al, 2014) we demonstrated good reliability using a rigid plate attached directly to the sternum, as suggested by wu et al (2005).…”
Section: Introductionmentioning
confidence: 52%
“…In contrast, a number of other studies have been performed using a set of skin-mounted markers placed at a range of different locations on the thorax (Seay et al, 2008;Mason et al, 2014). In a recent study (Mason et al, 2014) we demonstrated good reliability using a rigid plate attached directly to the sternum, as suggested by wu et al (2005). However, this configuration can also be difficult to track continuously with passive motion capture system, especially at higher speeds when increased arm movements can obscure sternum markers.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations